Evaluation of the 1000 renal transplants carried out at the University Hospital of the Botucatu Medical School (HCFMB) - UNESP and their evolution over the years - Nga, Hong Si (2018)
ABSTRACTIntroduction: The progress in kidney transplantation has been evident over the years, as well as its benefits for patients.Objectives: To evaluate the 1.000 kidney transplants performed at the Botucatu Medical School University Hospital, subdividing the patients in different periods, according to the current immunosuppression, and evaluating the differences in graft and patient survival.Methods: Retrospective cohort analysis of the transplants performed between 06/17/87 to 07/31/16, totaling 1,046 transplants, subdivided into four different periods: 1) 1987 to 2000: cyclosporine with azathioprine; 2) 2001 to 2006: cyclosporine with mycophenolate; 3) 2007 to 2014: tacrolimus with antimetabolic; and 4) 2015 to 2016: tacrolimus with antimetabolic, with increased use of the combination of tacrolimus and mTOR inhibitors.Results: There was an increase in the mean age of recipients and increase in deceased donors and their age in the last two periods. There was a reduction in graft function delay, being 54.3% in the fourth period, compared to 78.8% in the first, p = 0.002. We found a reduction in acute rejection, being 6.1% in the last period compared to 36.3% in the first, p = 0.001. Urological complications and diabetes after transplantation were more frequent in the first two periods. The rates of cytomegalovirus infection were higher in the last two periods. There was an improvement in graft survival, p = 0.003. There was no difference in patient survival, p = 0.77 (Figure 2).Conclusion: There was a significant increase in the number of transplants, with evolution in graft survival, despite the worsening in the profiles of recipients and donors.